Ergonomics as Determinant of Workplace Attitude of Librarians in Federal Universities in Southern Nigeria - Asaolu Aderonke O.; Ikonne Chinyere N. (COVENANT JOURNAL OF LIBRARY AND INFORMATION SCIENCE, 2022)
Purpose: The study was carried out to examine the influence of ergonomics and its attendant symptoms on workplace attitude of librarians in federal university libraries in Southern Nigeria. Methodology: The research design adopted for the study was survey design. The population of the study was made collection of three hundred and seventeen (317) librarians from the 17 federal universities in southern Nigeria. Total enumeration technique was adopted for the study. The instrument for data collection was structured and validated questionnaire that was distributed to the 317 librarians that work in the federal universities in southern Nigeria but only 294 (92.7%) were found useable. Data gathered from this research study was analyzed using both Findings: Though the workstations were ergonomically compliant, some of the librarians still experience ergonomic symptoms at the lower back. Some also experience this at the shoulders, upper back, ankle/feet, knee, wrist/hands, and at the elbows. This connotes that some librarians in federal universities in southern Nigeria experienced ergonomic symptoms in diverse areas of the body such as lower back, shoulders, upper back ankle/feet, knee, wrist/hands and at the elbows. It was also found that that the ergonomics symptoms librarians experience do not influence their work attitude negatively. Originality/Value: The study increases scientific knowledge on the impact of ergonomics on workplace attitude from the university library perspective.